GWAS of Suicide Attempt in Psychiatric Disorders and Association With Major Depression Polygenic Risk Scores - Mullins, Niamh; Bigdeli, Tim B; Børglum, Anders D; Coleman, Jonathan R I; Demontis, Ditte; Mehta, Divya; Power, Robert A; Ripke, Stephan; Stahl, Eli A; Starnawska, Anna; Anjorin, Adebayo; M.R.C.Psych; et al. (The American journal of psychiatry, 2019)
OBJECTIVE: More than 90% of people who attempt suicide have a psychiatric diagnosis; however, twin and family studies suggest that the genetic etiology of suicide attempt is partially distinct from that of the psychiatric disorders themselves. The authors present the largest genome-wide association study (GWAS) on suicide attempt, using cohorts of individuals with major depressive disorder, bipolar disorder, and schizophrenia from the Psychiatric Genomics Consortium. METHODS: The samples comprised 1,622 suicide attempters and 8,786 nonattempters with major depressive disorder; 3,264 attempters and 5,500 nonattempters with bipolar disorder; and 1,683 attempters and 2,946 nonattempters with schizophrenia. A GWAS on suicide attempt was performed by comparing attempters to nonattempters with each disorder, followed by a meta-analysis across disorders. Polygenic risk scoring was used to investigate the genetic relationship between suicide attempt and the psychiatric disorders. RESULTS: Three genome-wide significant loci for suicide attempt were found: one associated with suicide attempt in major depressive disorder, one associated with suicide attempt in bipolar disorder, and one in the meta-analysis of suicide attempt in mood disorders. These associations were not replicated in independent mood disorder cohorts from the UK Biobank and iPSYCH. No significant associations were found in the meta-analysis of all three disorders. Polygenic risk scores for major depression were significantly associated with suicide attempt in major depressive disorder (R2=0.25%), bipolar disorder (R2=0.24%), and schizophrenia (R2=0.40%). CONCLUSIONS: This study provides new information on genetic associations and demonstrates that genetic liability for major depression increases risk for suicide attempt across psychiatric disorders. Further collaborative efforts to increase sample size may help to robustly identify genetic associations and provide biological insights into the etiology of suicide attempt.
Keywords: Male; multifaktoriální dědičnost; Risk Factors; Schizophrenia; Depressive Disorder, Major; Polygenic Risk Scoring; Genome-Wide Association Study; Case-Control Studies; mužské pohlaví; Mood Disorders; Psychiatric Genomics Consortium; pokus o sebevraždu; lidé; Suicide; ženské pohlaví; studie případů a kontrol; Suicide, Attempted; Humans; schizofrenie; depresivní porucha unipolární; rizikové faktory; Female; bipolární porucha; Multifactorial Inheritance; celogenomová asociační studie; Bipolar Disorder